2021
DOI: 10.1088/1748-9326/abee4e
|View full text |Cite|
|
Sign up to set email alerts
|

A review of trends and drivers of greenhouse gas emissions by sector from 1990 to 2018

Abstract: Global greenhouse gas (GHG) emissions can be traced to five economic sectors: energy, industry, buildings, transport and AFOLU (agriculture, forestry and other land uses). In this topical review, we synthesise the literature to explain recent trends in global and regional emissions in each of these sectors. To contextualise our review, we present estimates of GHG emissions trends by sector from 1990 to 2018, describing the major sources of emissions growth, stability and decline across ten global regions. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
309
0
26

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 673 publications
(337 citation statements)
references
References 177 publications
2
309
0
26
Order By: Relevance
“…Since 2010, energy intensity and total carbon emissions have declined most sharply in countries that had adopted a wide raft of strengthened policies on energy efficiency across all sectors (140). Lamb et al (139) showed this occurred across all sectors for all regions of the world. Indeed, Maamoun (141), using extensive econometric analysis, showed how participating in the Kyoto Protocol led to an average increase in national CO 2 reductions of 7%.…”
Section: Net Impacts Of Energy Efficiency Policies On Energy Use: Macro Evidencementioning
confidence: 93%
See 1 more Smart Citation
“…Since 2010, energy intensity and total carbon emissions have declined most sharply in countries that had adopted a wide raft of strengthened policies on energy efficiency across all sectors (140). Lamb et al (139) showed this occurred across all sectors for all regions of the world. Indeed, Maamoun (141), using extensive econometric analysis, showed how participating in the Kyoto Protocol led to an average increase in national CO 2 reductions of 7%.…”
Section: Net Impacts Of Energy Efficiency Policies On Energy Use: Macro Evidencementioning
confidence: 93%
“…Evaluating the impact of energy efficiency and related policies on actual energy consumption presents a challenge: determining what would have happened in the absence of the policy (i.e., what is the counterfactual). A comparison across regions seems indicative that the trend of global energy efficiency (using energy intensity as its proxy, with all the caveats already described in Sections 2 and 3) has accelerated somewhat since the early to mid-2000s, in parallel with both rising energy prices and a rapid expansion of energy policies associated with rising climate change concerns and international commitments (139). The decomposition analysis in Reference 139, consistent with much other data, makes it clear that at least three-quarters of these emission savings were due to energy intensity improvements rather than to decarbonizing energy supply.…”
Section: Net Impacts Of Energy Efficiency Policies On Energy Use: Macro Evidencementioning
confidence: 99%
“…While there is a growing number of countries today on a sustained emission reduction trajectory (Lamb et al, 2021b;Le Quéré et al, 2019a), it is important to study the drivers of these reductions as well as patterns of emission growth in other parts of the world (Lamb et al, 2021a). Our analysis further reveals that there are no global sectors that show sustained reductions in GHG emissions.…”
Section: Discussionmentioning
confidence: 89%
“…Technological innovation and improvement have long been at the center of policies and approaches to improving the energy performance and reducing the energy consumption of buildings, but technology alone will not achieve their energy-saving goals. People and their energy behaviors in buildings must be included in the research and measures to improve energy efficiency [16]. This leads to the second approach, by which energy saving in office buildings is obtained through changes in the individual behaviors of employees.…”
Section: Emerging Importance Of Human Behavior As Energy Saving Factormentioning
confidence: 99%